PENGARUH KINERJA PEGAWAI DAN FASILITASPERPUSTAKAAN TERHADAP KEPUASAN MAHASISWADI PERPUSTAKAAN UNIVERSITAS KHAIRUN TERNATE - Zulaiha Husen; Nursia Nursia (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2018)
The purpose of this study is to determine the Influence and Employees and Library Space in general or simultaneously to the Student Satisfaction at the University Library Khairun Ternate. The analysis model used to test multiple linear regression hypothesis, and research method which is the research with the number of samples and the number of respondents as much as 99 respondents. With data processing techniques using SPSS 16 for windows. The results of the study found that: (1) Employee Performance has a positive and significant influence on student satisfaction in the library of Khairun University of Ternate, which means that the higher the employee performance, the higher the student satisfaction level, (2) The library facilities have a positive and significant impact on student satisfaction in the library of the University of Khairun Ternate, which means that with good facilities and adequate to provide learning outcomes to students, (3) Performance and Space Library against students at the University Khairun Ternate, which means that the higher performance and equipped with facilities adequate, the higher the level of student satisfaction in the library of Khairun University of Ternate. With the result of simultaneously both positive and significant variable to student satisfaction with R2 value (R Square) corrected by 0,559 or 55,9%.